2011
DOI: 10.1021/nl201826e
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Atomic Imaging of Colloidal Core–Shell Nanocrystals

Abstract: Colloidal core-shell semiconductor nanocrystals form an important class of optoelectronic materials, in which the exciton wave functions can be tailored by the atomic configuration of the core, the interfacial layers, and the shell. Here, we provide a trustful 3D characterization at the atomic scale of a free-standing PbSe(core)-CdSe(shell) nanocrystal by combining electron microscopy and discrete tomography. Our results yield unique insights for understanding the process of cation exchange, which is widely em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
128
2
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(140 citation statements)
references
References 38 publications
7
128
2
3
Order By: Relevance
“…57,58 Moreover, recent experiments have shown that ion exchange certainly proceeds in a layer-by-layer fashion, preventing a strong intermixing between Pb and Cd atoms. 59,60 Therefore, the well-resolved component seen on the Pb 5d core level at the lowest binding energy indicates that Pb exists in excess on the few PbSe facets at the surface of the HNCs and, possibly, on the CdSe surface of the shell. Such a hypothesis agrees with a recent study of the Pb 5d core-level spectrum measured for PbSe/CdSe HNCs with a complete shell that shows a shoulder at low binding energy, whereas, the PbO component was absent from the spectrum.…”
Section: Pbmentioning
confidence: 99%
“…57,58 Moreover, recent experiments have shown that ion exchange certainly proceeds in a layer-by-layer fashion, preventing a strong intermixing between Pb and Cd atoms. 59,60 Therefore, the well-resolved component seen on the Pb 5d core level at the lowest binding energy indicates that Pb exists in excess on the few PbSe facets at the surface of the HNCs and, possibly, on the CdSe surface of the shell. Such a hypothesis agrees with a recent study of the Pb 5d core-level spectrum measured for PbSe/CdSe HNCs with a complete shell that shows a shoulder at low binding energy, whereas, the PbO component was absent from the spectrum.…”
Section: Pbmentioning
confidence: 99%
“…In practice, atomic resolution STEM imaging of core/shell structures is only possible when the shell is a crystalline material, as the presence of an amorphous shell deteriorates the quality of the signal from the crystalline core. Examples of electron microscopy characterisation of semiconductor nanocrystals have included determination of their shape and size (McBride et al, 2004;Sahu et al, 2012;Bals et al, 2011;Ruberu and Vela, 2011), crystal structure (Soriano et al, 2012), examination of shell coverage (Yu et al, 2005;McBride et al, 2006) and chemical composition (Gunawan et al, 2011;McBride et al, 2006;Abel et al, 2012). Nonetheless, the number of high resolution electron microscopy studies of semiconductor nanocrystals is relatively sparse.…”
Section: Quantum Dots and Quantum Wiresmentioning
confidence: 99%
“…The reason that experimental results have been lacking until recently is that in all of the 2D projections, one should be able to determine the positions of the atom columns with great precision and in addition, one should be able to quantify the intensity in the images (TEM or STEM) in order to count the number of atoms in a column from a 2D projection. On the basis of the availability of new aberration-corrected microscopes in combination with advanced quantification methods, it was demonstrated recently that 3D reconstruction at the atomic scale is indeed feasible [94,95]. This will open up a new level of characterization at the (sub) nano scale.…”
Section: Quantification and Atomic Resolution Tomographymentioning
confidence: 99%